A Digitally Controlled RF/Optical Telephone System - Tzannidakis, Evangelos (My University, 1978)
This thesis discusses small size intercom networks. It is intended for, but not limited to, the use of optical fibre as the interconnecting medium.
Keywords: communication; telephone; fibre optic; fiber optic; cpu; intel